James Grant of Ballindalloch papers - Grant, James, 1720-1806.
Correspondence; diaries; military commissions; regimental returns; financial, land, and plantation records; parliamentary acts and speech; lists; maps and plans; and other papers documenting Grant's activities related to North America and the West Indies, including military service in the French and Indian War and the American Revolution, participation in military expeditions against Cherokee Indians in 1760-1761, his governorship of East Florida from 1763 to 1773, and his command of British forces in the West Indies from 1778 to 1780. Correspondents include British generals Charles Cornwallis, Marquis, and William Howe, Viscount, Prime Minister William Pitt, and George Washington.
Includes financial accounts of the colony of Nova Scotia from 1754 to 1758, business records from Grant's indigo plantation in East Florida from 1768 to 1783, MacPherson (McPherson) family papers relating chiefly to the service of family members in the French and Indian War and the American Revolution, and the Archibald Montgomery (Montgomerie) papers concerning Montgomery's command of the First Highland Battalion, including the regiment's service in North America.
Microfilm produced from originals in the National Archives of Scotland.
British army officer, colonial governor, and member of Parliament.
Collection material chiefly in English with French and Spanish.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Includes reels 1-50; reels 3 and 4 combined on one reel.
Keywords: Cornwallis, Charles Cornwallis, -- Marquis, -- 1738-1805 -- Correspondence; Howe, William Howe, -- Viscount, -- 1729-1814 -- Correspondence; Montgomerie, Archibald, -- 1726-1796; Pitt, William, -- 1759-1806 -- Correspondence; Washington, George, -- 1732-1799 -- Correspondence; McPherson family; Great Britain. -- Army. -- Highland Regiment, First; Cherokee Indians -- Wars, 1759-1761.; Indigo -- Florida; Plantations -- Florida; East Florida -- History; Florida -- History -- English colony, 1763-1784.; Great Britain -- Colonies -- America; Nova Scotia -- History -- 1713-1763.; United States -- History -- French and Indian War, 1754-1763 -- British forces; United States -- History -- Revolution, 1775-1783 -- British forces; West Indies -- History -- 1775-1783.; Army officers; Governors; Members of Parliament